Legalize It, Criticize It, or Something Else? Americans’ Attitudes Toward Federal Recreational Marijuana Legislation (RML) - Mancini, Christina (Crime & delinquency, 2024)
Recreational marijuana legislation (RML) has been enacted at the state-level but not federally. Given the link between public opinion and RML, we examine 2021 national poll (N?=?995) data that assessed views about different types of proposed federal actions concerning cannabis. Less than half of Americans preferred full legalization, 21% approved of medical legalization only, 23% believed in states? rights, and 11% supported the current prohibition. Using multinomial logistic regression modeling, respondents who associated legalized recreational marijuana with adverse/negative effects were less likely to favor full legalization. In contrast, respondents who associated legalized recreational marijuana with beneficial effects were most supportive of full legalization. Uncertainty surrounding cannabis shaped preferences but not as dramatically as having a clear opinion.